2022
DOI: 10.1080/21655979.2022.2060901
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0067741 regulates the Hippo/YAP pathway to suppress lung adenocarcinoma progression by targeting microRNA-183-5p

Abstract: To discuss the effect and molecular mechanism of circular RNA circ_0067741 on the occurrence and development of lung adenocarcinoma (LUAD). QRT-PCR was utilized to detect circ_0067741, microRNA-183-5p (miR-183-5p) and large tumor suppressor 1 (LATS1) expressions in tumor tissues of 30 LUAD patients and LUAD cell lines (A549, Calu-3, H1299 and H1975). After overexpression or knockdown of circ_0067741-1 or miR-183-5p in H1299 and A549 cells, respectively, cell proliferation, viability, apoptosis, invasion and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, a newly published study reported plasma miR-183-5p in CRC patients with lymph node metastasis was abnormally overexpressed ( 38 ). More importantly, Mo et al ( 39 ) found miR-183-5p plays an oncogenic role in lung adenocarcinoma by targeting LATS1 and inhibiting the Hippo/YAP pathway . When taken together, these findings suggest the multiple pathogenic roles of miR-183-5p in various human cancer types and its use in tumor staging might be closely linked with its specific binding to different target genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a newly published study reported plasma miR-183-5p in CRC patients with lymph node metastasis was abnormally overexpressed ( 38 ). More importantly, Mo et al ( 39 ) found miR-183-5p plays an oncogenic role in lung adenocarcinoma by targeting LATS1 and inhibiting the Hippo/YAP pathway . When taken together, these findings suggest the multiple pathogenic roles of miR-183-5p in various human cancer types and its use in tumor staging might be closely linked with its specific binding to different target genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circ_0072083 has been shown to promote LUAD cell proliferation, migration, and invasion by modulating FGB expression. Similarly, circ_0067741 has been shown to inhibit LUAD cell proliferation and invasion by ordering the Hippo signaling pathway [ 30 ]. In this project, we revealed that circ_16601 activated the Hippo pathway by increasing FGB expression and ultimately contributed to LUAD progression.…”
Section: Introductionmentioning
confidence: 99%